Assessment of attitude toward community service among dental students of Tertiary Care Teaching Hospital in South India - B Sujith Anand; K. V. N. R. Pratap; T Madhavi Padma; V Siva Kalyan; P Vineela; Surya Chandra Varma (Wolters Kluwer Medknow Publications, 2017)
Introduction: The dental health care providers and their community service in any nation play a pivotal role in bridging the gap between the oral health care and social service system. Understanding that there is a shortage and disparity in the oral health services provided, a greater emphasis on its awareness and education is the present need; thus, the aim of the study is to assess the attitude toward community service among dental students. Methodology: A cross-sectional questionnaire-based study was conducted among undergraduate dental students who were present on the day of study, and their attitude toward community service was assessed using a standardized Community Service Attitude Scale which consists of eight domains. Data were analyzed using descriptive statistics, Chi-square test, and ANOVA. The level of significance was set at P < 0.05. Results: The total participants included were 171. The levels of attitude toward community service among the study participants based on year (P = 0.0492), gender (P = 0.00482), and voluntary activity (P = 0.042) were found to be statistically significant. Conclusion: The attitude toward community service is influenced by gender and year of study. Hence, any practical training program with regard to service learning in their undergraduate curriculum would highly contribute to influence their attitude toward community service.